2006
DOI: 10.1590/s0066-782x2006001600015
|View full text |Cite
|
Sign up to set email alerts
|

Parâmetros diretos do duplex scan no diagnóstico da estenose da artéria renal: estudo de validação e otimização dos pontos de corte

Abstract: OBJECTIVETo test the efficiency of the direct duplex scanning parameters in the diagnosis of renal artery stenosis (RAS), and verify whether or not the cut-off points recommended by medical literature are the most appropriate means to distinguish lesion severity. METHODSProspective study, including 62 patients with RAS, submitted to a duplex ultrasound scan and selective arteriography. The peak systolic velocity (PSV) and the renal-aortic ratio (RAR) were measured. Statistical analysis included the ROC (receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Most studies reported sensitivity (n = 24/25) 3,5,12,14,24-29,30-39,40-43 and specificity (n = 24/25). 3,5,12,14,24-29,30-39,40,41,43,44 Nine of 24 studies reported exclusively high sensitivity (range: 90%-100%) 29,33,34,37,38,40,41,45 and 13 of 25 reported high specificity (range: 81%-100%). 3,14,24,29-31,33,34,37,38,40,…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Most studies reported sensitivity (n = 24/25) 3,5,12,14,24-29,30-39,40-43 and specificity (n = 24/25). 3,5,12,14,24-29,30-39,40,41,43,44 Nine of 24 studies reported exclusively high sensitivity (range: 90%-100%) 29,33,34,37,38,40,41,45 and 13 of 25 reported high specificity (range: 81%-100%). 3,14,24,29-31,33,34,37,38,40,…”
Section: Resultsmentioning
confidence: 99%
“…Twelve of 25 studies reported accuracy as a main outcome. 12,14,[24][25][26][27][28][29][30][31]32,33 Six of those 12 studies reported high agreement with CVA, 14,30,33 SRA, 25,29 and MRA 24 (range: 81-98%). The remaining 6 of 12 studies reported either moderate, 28 low, 31 or a combination of the degree of agreement depending on the DUS parameter.…”
Section: Dus Versus Other Angiography Techniquesmentioning
confidence: 98%
See 2 more Smart Citations
“…Therefore, hemodynamics can be monitored with ultrasound through the velocity tracing. Apart from pulsatility index (PI) and resistant index (RI)1518, peak systolic velocity (PSV) and ratio of PSV at stenosis to PSV at proximal artery are generally regarded as the important indexes in predicting stenosis and its severity 1924. However, the valve of velocity is related to many factors such as the site of sampling and the correction angle.…”
Section: Introductionmentioning
confidence: 99%